Work-Based Education as a Pathway to Resilience - Versnel, Joan; ., Jennifer de Lugt; ., Nancy L. Hutchinson; ., Peter Chin (Journal of Education and Vocational Research, 2011)
The purpose of this study was to explore the potential of work-based education (WBE) as a pathway for enhancing resilience among youth-at-risk for disengaging from school. For students who have experienced traditional academic school as an adverse context, the decision to pursue an alternative path to high school completion, for example WBE, can be interpreted as agentic. We propose that WBE may have the requisite features of an educational context that fosters resilience in at-risk youth. We used a multipleperspective case study method involving three young people in their final stages of secondary school. The students were the focal participants in each case. Each was interviewed and observed on multiple occasions. We interviewed teachers and workplace supervisors associated with each student for additional perspectives. Cases were analyzed individually, followed by cross-case analyses utilizing a resilience framework. Our study revealed evidence that for the three youth we studied, WBE had many elements that appear to enhance resilience in a way that academic programs did not. WBE kept these students engaged in the school context and contributed to the eventual successful completion of secondary school for all three. Choosing WBE as a pathway to secondary school completion can be an agentic act by at-risk youth to achieve graduation. Engagement in WBE also appears to enhance resilience. WBE may foster resilience in at-risk youth, who despite academic adversity, progress to completion. Graduation from secondary school is frequently identified as a positive outcome and a predictor of success in productive occupation and adult life.